Deltas in dialogue: Imagining policy transfer from the Netherlands to Vietnam and Bangladesh as a symmetrical conversation. (27th September 2021) - Hasan, Shahnoor; Evers, Jaap; Verzijl, Andres; Zwarteveen, Margreet
Abstract: Based on the in‐depth study of the travels of the Dutch Delta Plan—a water‐centered strategic long‐term plan to help prepare for the effects of climate change—to Vietnam and Bangladesh, this article reflects on ways to conceptualize processes of policy transfer. Such processes involve a range of actors and actions, and hinges on the quality of the interactions and (historic) relations between them. All involved contribute experience and knowledge, working in collaboration with each other to somehow—through translation and mutual learning—create a version of the transferred policy that fits its new context. We use the article to imagine policy transfer processes in less hierarchical and more reciprocal terms, not a priori positioning those originating the transfer as superior or more advanced than those on the receiving end. To do this, the article proposes a conceptualization of policy transfer processes as symmetrical conversations: conversations in which many knowers and knowledges are mixed together to co‐produce plans and policies that are relevant and specific. Beyond better acknowledging the importance of the receivers, we hope that this conceptualization will also open up the discussion about what "good" policies (or policy knowledges) are, as well as allow for more explicit reflection about how different knowledges and knowers relate to each other in policy transfer processes. This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance Abstract : Making waves: deltas in dialogue.